KOMPARASI KEMANDIRIAN BELAJAR MAHASISWA STAB KERTARAJASA PADA PEMBELAJARAN LURING DAN DARING - Febrianto, Andika; Murdana, Kadek Yudi; Kamanitra, Rakyan Paranimmita Sapurisa (Syailendra Buddhist College / Sekolah Tinggi Agama Buddha (STAB) Syailendra, 2021)
This research examines the learning independence of STAB Kertarajasa students. At first, STAB Kertarajasa implemented an offline learning process, but after the Covid-19 pandemic, the learning was carried out online. This research aims to determine the comparative of student learning independence in offline and online learning. This study uses quantitative research methods type comparative research. Respondents in this research were students of 6th Semester Academic Year 2020/2021 totaling 40 students. The data collection instrument used a questionnaire that had been tested for validity and reliability before being submitted to the main respondents. Analysis of the data in this research using a Likert Scale and the correlation test using the t-test. The results showed that students' learning independence in online learning had a total score of 2693, in the very high category. While offline learning has a total score of 2273, in the high category. Judging from the average student learning independence in online learning is 67,3250, while the average student learning independence with offline learning is 56.8250. This shows that the average value of student learning independence with online learning is higher than the average value of student learning independence with offline learning.